Augmented Reality and Animation Supported-STEM Activities in Grades K-12: Water Treatment - Necla Dönmez Usta; Neslihan Ültay (Universitas Pendidikan Indonesia, 2022)
Animation is used to increase the interest and engagement of students in the learning environment. Animation is exciting and fun, and using animation, abstract concepts are easy to present, display, and convey to students. Augmented reality, like animation, can help make it easier to understand abstract concepts. In many areas, augmented reality is used in education since it perfectly integrates virtual content with the natural world. STEM education is one of the areas where augmented reality can be used effectively. In this context, this research aimed to reveal the fourth-grade students' opinions about augmented reality and animation-supported STEM activities on the